Lp-Approximation (p≥1) by q-Kantorovich Operators. (15th May 2014) - Finta, Zoltán
Abstract : For a newq -Kantorovich operator we establish direct approximation theorems in the spaceL p [ 0, 1 ], 1 ≤ p ≤ ∞, via Ditzian-Totik modulus of smoothness of second order.